The Role Of Parents In The Development Of Iq And The Formation Of Critical Thinking Ability In Children: Educational Psychological Perspective - Cecep Sobar Rochmat; Salwamia Valhani; Diva Tamasya Fatiha; Rosendah (Educan : Jurnal Pendidikan Islam, 2023)
Educational psychology is a science that discusses all psychological problems in the educational process (teaching and learning). In the learning process, it is necessary to instill a tradition of thinking well and positively, one of which is thinking critically from an early age. Practicing curiosity about something will hone critical thinking patterns. When individuals think, what is needed is an intelligence quotient (IQ) to find out how much level a person has in applying critical thinking. This study aims to elaborate on how important parents' role is in developing IQ and forming necessary thinking skills in children. Critical thinking is a very important thinking skill because it is useful for solving problems in life. The method used in this study is library research, which collects data with textual sources in journals, articles, and books related to the discussion. The results showed that from the perspective of Educational Psychology, the role of parents is very significant in developing IQ and shaping critical thinking skills. Several main views are used: biological, behaviorism, cognitive, psychoanalysis and phenomenological perspectives. Therefore, in forming IQ and critical thinking skills, there needs to be habituation and experimentation with children's mindsets such as giving questions, giving conclusions, and trying to research something that is unknown. This research is expected to educate parents to understand child psychology better.